Acceptability and willingness to participate in the Tailored Activity Program: perceptions of people living with dementia, their care partners and health professionals. Issue 3 (28th December 2020) - Bennett, Sally; Travers, Catherine; Liddle, Jacki; Smith, Sandra; Clemson, Lindy; O'Reilly, Maria; Allen, Michelle; Laver, Kate; Beattie, Elizabeth; Low, Lee-Fay; O'Connor, Claire; Gitlin, Laura N.
Abstract: Objectives: The Tailored Activity Program (TAP) is an evidence-based occupational therapist-led intervention for people living with dementia and their care partners at home, developed in the USA. This study sought to understand its acceptability to people living with dementia, their care partners, and health professionals, and factors that might influence willingness to participate prior to its implementation in Australia. Methods: This study used qualitative descriptive methods. Semi-structured interviews were conducted with people living with dementia in the community ( n = 4), their care partners ( n = 13), and health professionals ( n = 12). People living with dementia were asked about health professionals coming to their home to help them engage in activities they enjoy, whereas care partners' and health professionals' perspectives of TAP were sought, after it was described to them. Interviews were conducted face-to-face or via telephone. All interviews were recorded and transcribed. Framework analysis was used to identify key themes. Results: Analysis identified four key themes labelled: (i) TAP sounds like a good idea; (ii) the importance of enjoyable activities; (iii) benefits for care partners; and (iv) weighing things up. Findings suggest the broad, conditional acceptability of TAP from care partners and health professionals, who also recognised challenges to its use. People living with dementia expressed willingness to receive help to continue engaging in enjoyable activities, if offered. Discussion: While TAP appeared generally acceptable, a number of barriers were identified that must be considered prior to, and during its implementation. This study may inform implementation of non-pharmacological interventions more broadly.